Akad Syariah pada Produk Pembiayaan BMT Mitra Arta Pekanbaru: Tinjauan Fatwa DSN-MUI - Yoga Riski Andria; Azwar; Samsia Afriani; Cinto Hasanah Fitri; Muhammad Fahrizal; Raihan Maulidil Ahmad (Genius: Jurnal Ekonomi Dan Manajemen, 2026)
Amidst these developments, Baitul Maal wat Tamwil (BMT) plays a strategic role as a micro-institution that performs business (tamwil) and social (maal) functions to empower the community's economy. The conformity of the application of contracts with Sharia principles regulated by the fatwa of the National Sharia Council Indonesian Ulema Council (DSN-MUI) is very important for the validity of transactions conducted at BMT. The conformity of transactions with Sharia principles established by the fatwa of the National Sharia Council Indonesian Ulema Council (DSN-MUI) is very important for the validity  transactions at BMT. The purpose of this research is to examine how murabahah, musyarakah, ijarah, and ijarah multijasa contracts are applied to financing products at BMT Mitra Arta Pekanbaru and to review their compliance based on the perspective of DSN-MUI fatwas. The main focus of the research is to ensure that the contract practices in the field meet the stipulated requirements to avoid elements of riba, gharar, and maisir. This research uses a qualitative approach with a descriptive research type thru field studies. Data were collected thru thorough interviews with relevant individuals, in addition to documentation, which consists of product brochures and other supporting documents. A comparative descriptive analysis method was used to compare practices at BMT Mitra Arta Pekanbaru with DSN-MUI fatwas number 04 (Murabahah), 08 (Musyarakah), 09 (Ijarah), and 44 (Ijarah Multijasa). The research results show that BMT Mitra Arta Pekanbaru has implemented murabahah, musyarakah, ijarah, and ijarah multijasa contracts in accordance with the provisions regulated in the DSN-MUI Fatwa